The idea of arbitration - Paulsson, Jan (Oxford : Oxford University Press, 2014)
Providing a theoretical examination of the concept of arbitration, this book explores the place of arbitration in the legal process and examines the ethical challenges to arbitral authority and its moral hazards.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 13, 2013).
Keywords: Arbitration, International